Analysis of Teacher Competence in Integrating Technology in The Learning Process in Banggai District - Wahyuni Wijayanti; Lukman A. R. Laliyo; Rustam I. Husain; Muhammad Rifai Katili; Maryam Rahim; Masri Kuadrat Umar (Postgraduate, University of Mataram, 2024)
The integration of technology in education not only trains learners to think critically and analyze information in depth, but also encourages them to become innovators and problem solvers. Local government and education stakeholders in Banggai district continue to improve teachers competencies in integrating technology in learning through various training programs. This research was conducted in education units in Banggai Regency. In this study, researchers used a type of quantitative research with a survey method. The sampling technique in this study will use cluster sampling technique. The sampling technique resulted in 690 respondents. This study uses the Rasch Model. From the results of the study, it was found that the competence of teachers in integrating technology in the learning process in Banggai Regency in terms of 8 sections obtained an average value from the highest to the lowest consecutively starting from Challenges in Technology Use of 1.57, Technical Skills of 0.43, Technological Knowledge of -0.04, Technological Pedagogical Knowledge of -0.06, Professional Development and Collaboration -0.08, Pedagogical Knowledge of -0.08, Content Knowledge of -0.32, and Effectiveness of Technology Use of -0.71. This indicates that teachers in Banggai district have a fairly high competency to integrate technology in learning